My Ghost Has a Name : Memoir of a Murder - Rossignol, Rosalyn (Book collections on Project MUSE., 2018)
"Author Rosalyn Rossignol journeys through the past to try and understand the murder of her childhood friend. Chapter One begins, "Murder is a crime ordinarily consigned to darkness: the shadowed alleyway, the murky gloom of midnight in someone's bedroom, the dimness of the forest. Just after 5:00 P.M. on October 20, 1999, on an afternoon that had been warm and sunny, but was now threatening rain, Deputy Kelly Cotner received a call from Beaufort County Dispatch to respond to the location 31 Bellinger Bluff Road in the area known locally as Lemon Island, but more often referred to as Okatie, in the coastal town of Bluffton, South Carolina. Cotner was at first told there was a gunshot victim on the premises; then, in route to the scene, he received clarification. The as yet "unknown victim" had been stabbed and beaten with a baseball bat."--